Multi-biomarker Approach as a Response of Oxidative Stress in Mytilus galloprovincialis (Lamarck, 1819) Obtained from the Algerian west coast - Belmokhtar, Rahma; Belmokhtar, Fayza; Kerfouf, Ahmed; Hamed, Mohammed Bey Baba (Marine Science Department Diponegoro University, 2024)
The present study aimed to assess the oxidative stress potential of Mytilus galloprovincialis across four sites along the Algerian west coast from March 2022 to June 2022. Among these sites, three were previously identified as contaminated, while the Barbadjanie site was considered isolated and distant from pollution sources. We measured glutathione (GSH) and malondialdehyde (MDA) levels, as well as the specific activities of glutathione S-transferase (GST) and catalase (CAT) in the digestive glands of the mussels. Our findings revealed a significant decrease in GSH levels in mussels from the contaminated sites, indicating reduced antioxidant capacity. In contrast, MDA levels, GST, and CAT activities exhibited significant increases (P< 0.05) in the same mussels, suggesting heightened oxidative stress and increased cellular damage. To further evaluate the impact of pollution, we applied the Integrated Biomarker Response (IBR) index to the four biomarkers measured. The IBR analysis showed the lowest score for mussels from Barbadjanie, confirming its relatively low pollution impact, and the highest score for mussels from Beni Saf Port, indicating severe pollution effects. This multi-biomarker approach was effective in demonstrating oxidative stress responses in mussels, highlighting its reliability in assessing the impacts of environmental pollution on aquatic organisms. The study underscores the importance of using comprehensive biomonitoring tools to evaluate ecological health and pollution effects in marine environments.